Magnetometry of the Scythian burial ground Katerinovka in the Lower Dnieper region - Bondar, K. M.; Daragan, M. M.; Prilukov, V.; Polin, S. V.; Tsiupa, I. V.; Didenko, S. V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2019)
The magnetometry of the Katerinovka burial ground (Nikopol district, Dnipropet-rovsk region, Ukraine) conducted on the area of 3.65 hectares showed three times more kurgans than they were visually detected or deciphered from satellite images. Archaeological excavations performed throughout the whole territory of geomagnetic survey area showed that most of the kurgans (24) belong to the Scythian epoch (IV century BC). There were also four burial mounds of the Golden Horde time (XIII—XIV centuries) and one — of the Bronze Age (beginning of the III millennium BC). Anomalies of magnetic induction (Bа) on the burial ground were mainly caused by objects deepened into the loess parent rock with magnetic susceptibility k = (0,3 ¸ 0,4) × 10–3 SI units and puddled with dark humus soil with k = (0.7 ¸ 0.9) × 10–3 SI units. The structural elements of the kurgans — pits, catacombs, ditches, and near-kurgan grooves — create weak (2—10 nT) anomalies of geomagnetic induction, which are reliably recorded using cesium magnetometers even under conditions of intense manmade interference from a heavy machinery in a quarry nearby. The fact of the existence of the near-kurgan grooves, from where the soil was taken to pour the Scythian mounds, was discovered for the first time from magnetometry results. The Bronze Age kurgan was identified by the semiring Bа anomaly from the groove 15—20 m wide. Among 10 burials, only two, the deepest ones, have created Bа anomalies with an intensity of 1.5—5.4 nT. Golden Horde kurgans were defined on the Bа map by weak ring anomalies from the ditches, as well as from the burnt bricks heaps covering some burials. The results of geomagnetic survey and archaeological excavations on the anomalies proved the inter-kurgan space of the visible mounds to be full of smaller sized and worse preserved kurgans. It has been shown that there is an urgent need to use high-resolution magnetometry at registering and studying the kurgan monuments of Ukraine, especially in areas of intensive industrial and agricultural land use.